Degradação eletroquímica da vinhaça usando eletrodo de diamante dopado com boro - Batista,Eveline Cristine (2011)
The degradation of vinasses in aqueous solution from ethanol industry has been investigated by electrochemical oxidation using a boron doped diamond electrode (BDD). Samples of vinasses were electrolyzed in medium of (0.1 mol L-1) Na2SO4 solutions at controlled potentials of +2.4, +3.0 and +4.0 V (vs. Ag/AgCl) and exhibited considerable reduction of total organic carbon. The cyclic voltammetry studies indicate that the vinasses are oxidized irreversibly over the BDD at 2.0 V (vs. Ag/AgCl) in diffusion controlled process. From the experimental results it is clear that the BDD electrode can be a valuable tool to the electrochemical degradation of vinasses in practical applications